Compensated compactness for a hyperbolic system of balance laws with three equations (2013)
We consider the problem studied by Lu et. al. in [Proc. Am. Math. Soc. 131, 3511 (2003)] to which we add a source term. This is a system of three balance laws. We use standard techniques, such as viscous approximations and compensated compactness, to prove the existence of solutions.